Teaching Politeness of Using Slang in Speaking: Analysis of Conversations in Tuesdays with Morrie - Rahmaniah, Sovia (Universitas Islam Negeri Antasari Banajarmasin, 2018)
Slang language is commonly used in American society in their daily life communication. However, teachers are still hesitant to teach slang in their speaking class, because slang language is assumed as impolite language. Most of the teachers donât realize that even slang language can be used in polite conversation. This paper is intended to show some analysis on some conversations in the movie entitle âTuesdays with Morrieâ which are assumed as the representation of social language for American. The focus of the analysis is the use of slang in polite conversations. The analysis will be based on the identification of a communicative event along with three dimensions called field, tenor, and mode. The significance of the study is to clarify teachersâ understanding toward slang language that can be assumed as a politeness, so the teachers will not hesitate to teach slang language to their students in speaking class. Furthermore, through this analysis, the students will know why, when, where, and how to use slang politely in their daily life conversation.